2016
DOI: 10.18410/jebmh/2016/500
|View full text |Cite
|
Sign up to set email alerts
|

Medullary Carcinoma of Breast: Clinicopathological Study

Abstract: To study the clinical and histopathological features of medullary breast carcinoma (MBC) in rural population in Western Maharashtra. MATERIALS AND METHODS This is a retrospective, analytic study which is done at a tertiary care hospital from March 2010 to April 2016 for a period of 6 years. RESULTS Total of 241 consecutive cases of breast malignancy surgically operated for mastectomy or modified radical mastectomy were studied. From these 241 cases, 11 were reported as medullary carcinoma (constitute 4.56%). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Typically MBCs are almost invariably triple hormone receptor negative, although some typical and atypical MBCs are ER, PR and/or HER-2 positive, indicating the heterogeneity of this type of breast carcinomas. 13 In our study IHC showed triple negativity in 75% cases of MBC (Fig 3) with majority of in typical MBC (80%) similar to study conducted by Jagtap et al 1 .Of the two cases of atypical MBC, one case was ER, PR positive, while Her 2/neu negativity was noted in both.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Typically MBCs are almost invariably triple hormone receptor negative, although some typical and atypical MBCs are ER, PR and/or HER-2 positive, indicating the heterogeneity of this type of breast carcinomas. 13 In our study IHC showed triple negativity in 75% cases of MBC (Fig 3) with majority of in typical MBC (80%) similar to study conducted by Jagtap et al 1 .Of the two cases of atypical MBC, one case was ER, PR positive, while Her 2/neu negativity was noted in both.…”
Section: Resultssupporting
confidence: 86%
“…10 16.7%, similar to study conducted by Jagtap (Figure 2 F, G). The incidence of atypical MBC was et al 1 Histopathological categorization of atypical www.pacificejournals.com/apalm eISSN: 2349-6983; pISSN: 2394-6466 46%) than in those with atypical medullary carcinomas (30%-52%) or invasive ductal carcinomas (29%-65%). 12 In our study, the number of positive metastatic lymph node involvement were more in atypical MBC (50%) compared to typical MBC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations